Perdagangan Orang: Ancaman Nyata, Upaya Hukum dan Pencegahannya di Desa Tirtayasa Serang Banten - Muhamad Romdoni; Reine Rofiana (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Human Trafficking is a transnational crime, this is because human trafficking involves many countries in terms of planning, real actions and the consequences. The countries targeted are not only developed countries but developing countries such as Indonesia are not immune to this crime. Real evidence can be found in one of the areas in Banten province, namely Tirtayasa Village located in Serang Regency. Many residents think that by going abroad they can change their fate in the village, without thinking about the legal or illegal process. As a result, there are several residents who experience physical violence and not being paid their wages. Therefore, it is necessary to hold comprehensive socialization activities related to human trafficking which include real actions, legal efforts and prevention efforts. The results of this socialization show that the knowledge of village communities who assume that if they can work abroad it will change their fate is a misguided perception. Because in this socialization, the legal and illegal processes related to the departure of migrant workers from Indonesia abroad are conveyed. With this socialization, village communities know that the law will protect them wherever they go as long as they are law-abiding citizens. Furthermore, it is hoped that this activity can be continued by village officials so that it can be a filter for its residents before they dare to work abroad.